Analysis of Some Trace Metals in Fish Species after Preconcentration with Congo Red on Amberlite XAD-7 Resin by Flame Atomic Absorption Spectrometry - Alpdogan, Guzin; San, Nevim; Zor, Sule Dinc (HINDAWI LTD, 2016)
A new procedure for separation and preconcentration of trace amounts of Cu(II), Ni(II), Fe(III), Zn(II), Cr(III), Cd(II), and Pb(II) in fish samples was proposed. The procedure is based on the adsorption of these metal ions on the column of Amberlite XAD-7 as congo red complexes prior to their determination by flame atomic absorption spectrometry (FAAS). Several factors that can affect the sorption and elution efficiency of the metal ions were investigated and optimized. The sorption was quantitative in the pH range of 6.0-9.0 for Cu(II) and Ni(II), 5.5-8.0 for Fe(III), 6.0-8.5 for Zn(II) and Cd(II), and 7.0-8.5 for Cr(III) and Pb(II). The optimum pH for simultaneous retention was 7.5. The sorption capacity of the resin was found to be 0.89, 0.72, 0.82, 0.61, 0.53, 0.84, and 0.78mg/g for Cu(II), Ni(II), Fe(III), Zn(II), Cr(III), Cd(II), and Pb(II), respectively. The precision of the method was evaluated as the relative standard deviation obtained by analyzing a series of six replicates and below 6% for all seven elements. The validation of the method was performed by the analysis of certified reference materials. The proposed method was successfully applied to separation/ preconcentration and determination of these metals in fish samples.
Keywords: SOLID-PHASE EXTRACTION; HEAVY-METALS; WATER SAMPLES; BIOLOGICAL SAMPLES; FOOD SAMPLES; IONS; SEPARATION; CADMIUM; COPPER; REMOVAL; Chemistry